Development of a prediction model for mortality and cardiovascular outcomes in older adults taking into account AZGP1 - Dörte Huscher (Nature Portfolio, 2021)
Abstract Zinc-alpha 2-glycoprotein (AZGP1) is a serum protein with postulated functions in metabolism, cancer and cardiovascular disease. We developed new prediction models for mortality or cardiovascular events investigating the predictive potential of serum AZGP1 in a community-based cohort of older adults. We measured AZGP1 (μg/ml) in stored serum samples of 930 individuals of the Berlin Initiative Study, a prospective, population-based cohort of adults aged ≥ 70. We determined the prognostic potential of 20 knowledge-based predictors including AZGP1 for the outcomes of mortality or the composite endpoint of death and cardiovascular events (stroke, myocardial infarction (MI)) using Cox models; their model fit was evaluated with calibration plots, goodness-of-fit tests and c-indices. During median follow-up of 48.3 months, 70 incident strokes, 38 incident MI and 234 deaths occurred. We found no associations or correlations between AZGP1 and other candidate variables. After multivariable Cox regression with backward-selection AZGP1 remained in both models for mortality (HR = 0.44, 95%CI: 0.24–0.80) and for the composite endpoint (HR = 0.43, 95%CI: 0.23–0.82). Within newly built prediction models, we found that increased AZGP1 levels were predictive for lower risk of mortality and the composite endpoint in older adults. AZGP1 as a predictor warrants further validation in older adults.